Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1021/jp0519767
|View full text |Cite
|
Sign up to set email alerts
|

Which Do Endohedral Ti2C80 Metallofullerenes Prefer Energetically:  Ti2@C80 or Ti2C2@C78? A Theoretical Study

Abstract: Four possible isomers of the Ti2C80 metallofullerene are discussed in detail at the B3LYP DFT level of theory: two isomers in Ti2@C80 formula with two Ti atoms encapsulated inside a C80 cage and the other two in Ti2C2@C78 formula with a Ti2C2 cluster involved inside a C78 cage. In the encaged Ti2C2 cluster, there are end-on and side-on C2 bridging modes into the two Ti atoms. The optimized end-on cluster has a linear Ti-C-C-Ti array, whereas the side-on cluster has a butterfly-like structure where the two Ti a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
52
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 30 publications
(36 reference statements)
5
52
0
Order By: Relevance
“…In the meantime, some endohedral complexes doped with various small molecules or ions have also been obtained [34][35][36][37][38][39][40][41][42][43][44][45][46][47]. For example, Gan [36] have reported the structures and stabilities of dimetallofullerenes M 2 @C n (M = Sc and La, n = 72, 76, 78, 80, and 84) with local density functional (LDA) method, and demonstrated that the two metallic atoms always tend to separate as long as possible inside fullerene cage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the meantime, some endohedral complexes doped with various small molecules or ions have also been obtained [34][35][36][37][38][39][40][41][42][43][44][45][46][47]. For example, Gan [36] have reported the structures and stabilities of dimetallofullerenes M 2 @C n (M = Sc and La, n = 72, 76, 78, 80, and 84) with local density functional (LDA) method, and demonstrated that the two metallic atoms always tend to separate as long as possible inside fullerene cage.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Gan [36] have reported the structures and stabilities of dimetallofullerenes M 2 @C n (M = Sc and La, n = 72, 76, 78, 80, and 84) with local density functional (LDA) method, and demonstrated that the two metallic atoms always tend to separate as long as possible inside fullerene cage. Yumura et al [39] have discussed the possible isomers of the Ti 2 @C 80 metallofullerene using the hybrid DFT-B3LYP functional, and found that Ti bindings over the hexagon ring are energetically preferable relative to those over a junction between hexagon and pentagon rings. Rehaman et al [44] have studied the pocket and antipocket conformations of CH 4 @C 84 using density functional theory (DFT) and second-order Møller-Plesset perturbation theory (MP2), and found that the antipocket conformation have an alternative minimum.…”
Section: Introductionmentioning
confidence: 99%
“…), [49][50][51][52][53] and there are theoretical and experimental indications that Ti 2 @C 80 is actually a Ti 2 C 2 @C 78 . [54][55][56] Recently, Sc 2 C 2 @C 68 with non-IPR carbon cage was isolated. 57 The studies of endohedral fullerenes have already reached the state when the survey of the whole field in one medium-size article is hardly possible.…”
Section: Introductionmentioning
confidence: 99%
“…Many other C 78 -based EMFs have been extracted successfully and most of them were determined to possess the IPR carbon cage D 3h (24109)ÀC 78 , such as La 2 @C 78 , [28,29] Ce 2 @C 78 , [30] Ti 2 C 2 @C 78 , [31][32][33][34] and Sc 3 N@C 78 . [35,36] In contrast, the major isomers of Dy 3 N@C 78 and Tm 3 N@C 78 were proposed to bear the same non-IPR carbon cage with Gd 3 N@C 78 .…”
mentioning
confidence: 99%